2019
DOI: 10.1371/journal.pone.0213502
|View full text |Cite
|
Sign up to set email alerts
|

Comparative metabolomic profiling in the roots and leaves in contrasting genotypes reveals complex mechanisms involved in post-anthesis drought tolerance in wheat

Abstract: Understanding the contrasting biochemical changes in different plant parts in response to drought can help to formulate smart strategies to develop drought tolerant genotypes. The current study used metabolomics and physiological approaches to understand the differential biochemical changes coupled with physiological adjustments in leaves and roots to cope with drought stress in two wheat genotypes, LA754 (drought tolerant) and AGS2038 (drought sensitive). The gas chromatography-mass spectrometry (GC-MS) analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(80 citation statements)
references
References 71 publications
4
73
2
1
Order By: Relevance
“…The upregulation of intermediates in the TCA cycle may reflect acceleration of the TCA pathway, suggesting that COR treatment could facilitate the flow of carbon from glycolysis to manufacture other defense compounds and produce more additional energy, such as NADH and ATP, to address oxidative stress. In addition, glyceric acid, a component of glycolysis, was associated with a greater ability to absorb nutrients and water of wheat under drought conditions [4]. The founding of Li et al indicated that exogenous ÎČ-sitosterol promoted the accumulation of glyceric acid contributing to improved drought tolerance in white clover [56].…”
Section: Exogenous Cor Enhances the Accumulation Of Organic Acids Undmentioning
confidence: 99%
See 1 more Smart Citation
“…The upregulation of intermediates in the TCA cycle may reflect acceleration of the TCA pathway, suggesting that COR treatment could facilitate the flow of carbon from glycolysis to manufacture other defense compounds and produce more additional energy, such as NADH and ATP, to address oxidative stress. In addition, glyceric acid, a component of glycolysis, was associated with a greater ability to absorb nutrients and water of wheat under drought conditions [4]. The founding of Li et al indicated that exogenous ÎČ-sitosterol promoted the accumulation of glyceric acid contributing to improved drought tolerance in white clover [56].…”
Section: Exogenous Cor Enhances the Accumulation Of Organic Acids Undmentioning
confidence: 99%
“…With global climate changes and increasing demands for food production, drought stress-related yield losses have received increasing attention in recent years [1,2]. From the stimulated grain crops modeling, more frequency to the arid extreme events are predicted to augment by the end of the twenty-first century, leading to severe water crisis and double the yield reduction in cultivation areas [3,4]. In addition to the decline of production, drought also triggers an array of morphological, physiological, and biochemical responses, including the inhibition of cell elongation and expansion, the disruption of major components of photosynthesis, the triggering of severe oxidative bursts, and even resulting in the death of the plants [5].…”
Section: Introductionmentioning
confidence: 99%
“…These can also be used to probe the prototype of any vital gene in plants and permit a genotypic-metabolic-phenotypic level of understanding. As compared to any other living organism, a diverse range of plant metabolites have different orders of instability, size, polarity, solubility, adaptability, and volatility [15][16][17][18]. Metabolomics, metabolic, or metabolite profiling terms are alternatively used to describe three kinds of approaches, such as targeted metabolomics, semi-targeted metabolomics, and untargeted metabolomics [1,7].…”
Section: Metabolomics: Significance In Plant Biologymentioning
confidence: 99%
“…The mass spectrometry technique provides the benefit of quick sample preparation and examination in their natural state [17]. Ultra-high-performance liquid chromatography (UPLC) and high-performance liquid chromatography (HPLC) are conventional tools for metabolite analysis.…”
Section: Advanced Tools For Analytical Research In Plant Metabolomicsmentioning
confidence: 99%
See 1 more Smart Citation